Fiscal spillovers in the euro area a model-based analysis - Maria-Grazia Attinasi; Magdalena Lalik; Igor Vetlov (European Central Bank (ECB), 2017)
The fiscal consolidation measures adopted in many euro area countries over 2010-13 reduced excessive domestic fiscal imbalances, but came at the cost of short-term output losses. This simultaneous tightening of fiscal policy raised concerns that such output losses might be exacerbated by negative spillovers from other countries. This paper presents some model-based simulations for the euro area with a view to gauge the cross-country impact of the fiscal measures adopted over 2010-13. The paper finds that the output effects of the fiscal consolidation were heterogeneous across countries, reflecting the different amounts and composition of fiscal measures adopted. We find that the trade channel is able to generate sizeable cross-border fiscal spillovers in the euro area. However, once the analysis takes into account the remaining channels (e.g. monetary policy reaction, exchange rate, and risk premium) total spillovers are estimated to be relatively small. In general, when compared to the growth fallout of domestic fiscal policies, negative fiscal spillovers do not seem to have added much to the economic growth woes of vulnerable countries.
Keywords: E42; E32; F42; F45; 330; fiscal consolidation; policy spillovers; macroeconomic models; euro area